2010
DOI: 10.1002/fld.2408
|View full text |Cite
|
Sign up to set email alerts
|

Shear effect on square cylinder wake transition characteristics

Abstract: SUMMARYThe transition of square cylinder wake flow from two-dimensional (2-D) to three-dimensional (3-D) when inflow is subjected to linear shear is examined numerically. The value of the non-dimensional shear parameter (K ) considered in this study are 0.0, 0.1, and 0.2. The range of Reynolds number (Re) defined based on the centerline velocity and cylinder width is from Re = 150 to 700. The transition of the wake flow from 2-D laminar to 3-D is marked by streamwise vortical structures. Unlike in uniform flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…This occurs as the flow becomes timeperiodic, but the downforce is not overcome, and average positive lift obtained, until after the flow has become three-dimensional for R > 3.1. The net downforce has also been reported for square cylinders in homogeneous upstream shear 49,71 for Re ≤ 100 and K ≤ 0.5, while for Re ≥ 150, positive lift has been observed 41,56 . Both observations are perfectly compatible with our results.…”
Section: Aerodynamic Performancessupporting
confidence: 56%
See 3 more Smart Citations
“…This occurs as the flow becomes timeperiodic, but the downforce is not overcome, and average positive lift obtained, until after the flow has become three-dimensional for R > 3.1. The net downforce has also been reported for square cylinders in homogeneous upstream shear 49,71 for Re ≤ 100 and K ≤ 0.5, while for Re ≥ 150, positive lift has been observed 41,56 . Both observations are perfectly compatible with our results.…”
Section: Aerodynamic Performancessupporting
confidence: 56%
“…The rate of increase of C l with K sharpens as Re gets larger, while C d becomes quite independent of K for Re > 200 4,55 . C l and C d fluctuations increase both with Re and with K at low Re ≤ 150 56 and even beyond 41 , but are mostly insensitive to K at higher Re 4,5 .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is because of the fact that the computational domain is finite, whereas the physical domain is infinite. We found that the convective boundary condition (Lankadasu and Vengadesan 2010) given in Eq. (7) is the best fit and provides the flow exit with the smooth discharge of vortices and minimizes the effect of outlet boundary on the flow near the cylinder than other boundary conditions.…”
Section: Governing Equationsmentioning
confidence: 99%